KARACİĞER METASTAZI İLE SEYREDEN MEDÜLLER TİROİD KARSİNOMU OLGU SUNUMU - ORAL, Ceyhun; ÜNAL, Ethem; Karataş, Adem (Cerrahpaşa Medical Journal, 2014)
Background.- Medullary thyroid carcinoma usually presents with palpable cervical lymphadenopathy, rapidly arising neck mass and local pain. Less frequently, dysphagia, dyspnea and dysphenia can be seen as a result of local invasion. However, especially in familial cases (MEN 2A, MEN 2B and nonMEN), chronic diarrhea can develop as the only symptom. Observation.- In the present study, we present a 25 year-old male patient with distant metastasis of medullary thyroid carcinoma. The diagnosis was confirmed after liver biopsy taken during diagnostic laparoscopy.